1990
DOI: 10.1111/j.1399-6576.1990.tb03057.x
|View full text |Cite
|
Sign up to set email alerts
|

Aortic surgery: effect of clonidine on intraoperative catecholaminergic and circulatory stability

Abstract: Twenty-eight patients presenting for aortic surgery were randomly assigned in a double-blind, placebo-controlled protocol to receive placebo (n = 14) or clonidine (4.7 +/- 1.2 micrograms.kg-1 po; n = 14), in addition to flunitrazepam 120 min before induction of anesthesia. Plasma catecholamines (CA) and hemodynamic variables were determined at 7 stages during surgery. In the placebo group, plasma epinephrine (E) and norepinephrine (NE) had risen twofold at skin closure compared to baseline (E: from 109 +/- 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
9

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 29 publications
(30 reference statements)
2
29
0
9
Order By: Relevance
“…Assim, parece ter ocorrido redistribuição do volume sangüíneo da vasculatura distal para a vasculatura proximal à oclusão aórtica, com aumento da pré-carga. Vários autores observaram aumento das pressões de enchimento durante o pinçamento aórtico [27][28][29] , enquanto outros autores não observaram essas alterações 30 . Por outro lado, muitos autores atribuem, como causa principal do aumento da pressão arterial média durante o pinçamento aórtico, o aumento súbito da impedância do fluxo aórtico, com aumento da pós-carga 31 , acompanhado, muitas vezes, por diminuição do índice cardíaco 27 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Assim, parece ter ocorrido redistribuição do volume sangüíneo da vasculatura distal para a vasculatura proximal à oclusão aórtica, com aumento da pré-carga. Vários autores observaram aumento das pressões de enchimento durante o pinçamento aórtico [27][28][29] , enquanto outros autores não observaram essas alterações 30 . Por outro lado, muitos autores atribuem, como causa principal do aumento da pressão arterial média durante o pinçamento aórtico, o aumento súbito da impedância do fluxo aórtico, com aumento da pós-carga 31 , acompanhado, muitas vezes, por diminuição do índice cardíaco 27 .…”
Section: Discussionunclassified
“…Na presente pesquisa, o índice de r e s i s t ê n c i a v a s c u l a r s i s t ê m i c a n ã o s e a l t e r o u significantemente em nenhum dos grupos estudados, durante o pinçamento aórtico. Quintin e col. 29 15,9 ± 16,9 14,3 ± 16,6 13,0 ± 13,8 8,4 ± 5,9* DCr (ml.min -1 .kg -1 ) GH 3,6 ± 1,2 4,0 ± 2,7 3,9 ± 2,4 3,9 ± 2,4 4,0 ± 2,0 GI 5,3 ± 4,9 4,4 ± 3,8 4,2 ± 2,7 3,3 ± 1,7 4,6 ± 2,5 GS 4,1 ± 1,6 4,5 ± 2,3 5,5 ± 4,4 5,2 ± 3,5 3,5 ± 2,3 36 . O fator natriuréti-co também pode diminuir a pressão arterial, ao relaxar a musculatura lisa vascular, e a estimulação simpática, e inibir o sistema renina-angiotensina-aldosterona e a liberação de hormônio antidiurético.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Thus, clonidine, as well as other alpha,-agonists, has a direct attenuating effect on the sympathetic nervous system. This in turn provides, for example, increased haemodynamic stability during surgery [3,4]. In animal studies clonidine and such novel alpha,-agonists as dexmedetomidine have been shown to possess potent anaesthetic properties.…”
Section: Sj Squires P1vmouth Pli 3jymentioning
confidence: 99%